ANALISIS PENILAIAN KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN ROKAN HILIR - Syaputra, Indra; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims are to identify and analyze employee performance evaluation in Health Departement of Rokan Hilir District and determine the factors that influence employee performance evaluation in Health Departement of Rokan Hilir District. The location of this research is in the Health Office Rokan Hilir District. The informants are formal leaders and informal leaders. Formal character is the head of Health Office of Rokan Hilir District, while the informal leaders that employees who are knowledgeable about research problems. In analyzing the data was used descriptive method that analyzes the data by formulating and decipher and interpret based on the basic theories are closely related to the existing problems. The study states that the aspect of individual attributes based on individual interviews to employee of Health Department Rokan Hilir mostly pretty good. Aspects of effort, is the work done and the desire to realize the business. Based on the interview, attributes of employee efforts in Rokan Hilir District Health Service is quite good. Aspects of organizational support, which includes leadership and work environment. Based on the interview organizational support in Health Service of Rokan Hilir District is quite good. Factors affecting employee performance evaluation is the thoroughness and fairness. Both superiors and employees in Health Office of Rokan Hilir District said it supported their performance assessment based on accuracy and fairness, and fair as it can support the creation of a better employee performance.Keywords: Assessment, Performance, Health Departmen